Operationalization of a District-Level Health Emergency Operation Center During the Mount Semeru Eruption: A Field Report - Yogadhita, Gde Yulian; Atriana, Dinda; Sutono, Sutono; Pangaribuan, Happy R; Wibowo, Bayu; Setiawati, Hani; Lestari, Sri; Fitriana, Ririn; Ramadhanjaya, Rakhmad; Hermawan, Dody; Oktafianto, Sonny (Universitas Gadjah Mada, 2026)
Introduction: Indonesia is highly prone to natural disaster, including volcanic eruptions that often generate sudden public health emergencies requiring rapid coordination and effective management of health resources. The eruption of Mount Semeru in December 2021 caused mass displacement and increased demand for emergency health services in Lumajang District, East Java. Objective: This field report aims to describe the establishment and operationalization of a district-level Health Emergency Operations Center (HEOC) during the acute response to the Mount Semeru eruption. Methods: A descriptive field report design was applied using operational documents, real-time coordination records, and field observations collected during the first ten days of the emergency response. Data were analyzed descriptively to examine coordination mechanisms, information management, volunteer deployment, and logistics monitoring. Results: HEOC activation strengthened command and coordination through routine coordination meetings, centralized health information management, structured volunteer deployment, and integrated logistics monitoring. These mechanisms improved situational awareness, reduced duplication of efforts, and supported timely operational decision-making despite resource constraints. Conclusion: The operationalization of a district-level HEOC enhanced health sector coordination and operational efficiency during the acute response phase. This report provides practical insights into HEOC implementation and highlights its importance for strengthening district-level health emergency preparedness in disaster-prone settings.